Early or late cranioplasty following decompressive craniotomy for traumatic brain injury: A systematic review and meta-analysis. Issue 7 (July 2018) - Zheng, Feng; Xu, Hao; von Spreckelsen, Niklas; Stavrinou, Pantelis; Timmer, Marco; Goldbrunner, Roland; Cao, Fang; Ran, Qishan; Li, Gang; Fan, Ruiming; Zhang, Qiang; Chen, Wei; et al.
Objective: To evaluate the effectiveness of early (<3 months) cranioplasty (CP) and late CP (>3 months) on post-operative complications in patients receiving decompressive craniotomy (DC) for traumatic brain injury (TBI). Methods: The Cochrane Library, PubMed and EMBASE databases were systematically searched for studies published prior to May 21, 2017. A meta-analysis examined post-operative overall complication rates, infection rates, subdural fluid collection and operating times according to early and late CP. Results: Of the initial 1675 references, five studies, all cohort, involving a total of 413 patients, were selected for the review. There was no difference between early and late CP in post-operative overall complication rate (RR=0.68, 95%CI [0.36, 1.29]) and the post-operative infection rate (RR=0.50, 95%CI [0.20, 1.24]) in patients receiving DC for TBI. However, there was a significant difference in post-operative subdural effusion (RR=0.24, 95%CI [0.07, 0.78]) and mean operative time (mean difference = −33.02 min, 95%CI [−48.19, −17.84]) both in favour of early CP. Conclusions: No differences were found between early and late CP in post-operative overall complications and procedural related infections in patients receiving DC for TBI, but early CP reduced the complication of subdural effusion and the mean operating time. These findings need to be confirmed by large, randomised controlled trials.